2012
DOI: 10.1021/ar300022h
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial Toxicity Testing in the 21st Century: Use of a Predictive Toxicological Approach and High-Throughput Screening

Abstract: Conspectus The production of engineered nanomaterials (ENMs) is a scientific breakthrough in material design and the development of new consumer products. While the successful implementation of nanotechnology is important for the growth of the global economy, we also need to consider the possible environmental health and safety (EHS) impact as a result of the novel physicochemical properties that could generate hazardous biological outcomes. In order to assess ENM hazard, reliable and reproducible screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
492
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 518 publications
(498 citation statements)
references
References 20 publications
(89 reference statements)
5
492
0
1
Order By: Relevance
“…Biochemical assays with a fluorometric or spectrophotometric read-out, including enzymatic and (enzyme-linked) immunoassays, are used to the utmost extend due to the relatively short duration of most assays, the uncomplicated detection principle and straight forward data processing 83 . Furthermore the possibility of upscaling and automation of the execution, detection and data processing make these assays highly convenient with regard to a future high content screening approach for every newly synthetized NP 83,84 . Another popular approach is staining the entire cell or specific cellular components with cellular dyes, fluorescently labeled antibodies (AB) or molecular probes, which will interact with a specific biomolecule 40,78,85 .…”
Section: A Routine In Vitro Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical assays with a fluorometric or spectrophotometric read-out, including enzymatic and (enzyme-linked) immunoassays, are used to the utmost extend due to the relatively short duration of most assays, the uncomplicated detection principle and straight forward data processing 83 . Furthermore the possibility of upscaling and automation of the execution, detection and data processing make these assays highly convenient with regard to a future high content screening approach for every newly synthetized NP 83,84 . Another popular approach is staining the entire cell or specific cellular components with cellular dyes, fluorescently labeled antibodies (AB) or molecular probes, which will interact with a specific biomolecule 40,78,85 .…”
Section: A Routine In Vitro Methodsmentioning
confidence: 99%
“…Since it was observed that NP can cause multiple effects via different mechanisms, awareness has risen on the necessity to evaluate nanotoxicity in vitro by a multiparametric method 43,83 .…”
Section: B Multiparametric Nanotoxicity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is therefore an urgent need to clarify the toxic effects of NPs and NMs and to elucidate the mechanisms involved in their toxicity. In view of the large number of NMs currently in use, high throughput screening (HTS) techniques aimed at accurately predicting and assessing toxicity are clearly needed; given the availability of reliable toxicity metrics, the HTS approach will generate large and valuable data sets 3, 4…”
Section: Introduction To High‐throughput Screening Of Nanomaterialsmentioning
confidence: 99%
“…HTS is defined as the use of automated tools to facilitate rapid execution of a large number and variety of biological assays that may include several substances in each assay 4. HTS was introduced in the pharmaceutical and chemical industries as a rapid way of evaluating effects of many novel compounds.…”
Section: Introduction To High‐throughput Screening Of Nanomaterialsmentioning
confidence: 99%